Religious beliefs and alcohol control policies: a Brazilian nationwide study - Lucchetti, Giancarlo (2014)
Objective: The connection between lower alcohol use and religiousness has been extensively examined. Nevertheless, few studies have assessed how religion and religiousness influence public policies. The present study seeks to understand the influence of religious beliefs on attitudes toward alcohol use. Methods: A door-to-door, nationwide, multistage population-based survey was carried out. Self-reported religiousness, religious attendance, and attitudes toward use of alcohol policies (such as approval of public health interventions, attitudes about drinking and driving, and attitudes toward other alcohol problems and their harmful effects) were examined. Multiple logistic regression was used to control for confounders and to assess explanatory variables. Results: The sample was composed of 3,007 participants; 57.3% were female and mean age was 35.7 years. Religiousness was generally associated with more negative attitudes toward alcohol, such as limiting hours of sale (p < 0.01), not having alcohol available in corner shops (p < 0.01), prohibiting alcohol advertisements on TV (p < 0.01), raising the legal drinking age (p < 0.01), and raising taxes on alcohol (p < 0.05). Higher religious attendance was associated with less alcohol problems (OR: 0.61, 95%CI 0.40-0.91, p = 0.017), and self-reported religiousness was associated with less harmful effects of drinking (OR: 0.61, 95%CI 0.43-0.88, p = 0.009). Conclusions: Those with high levels of religiousness support more restrictive alcohol policies. These findings corroborate previous studies showing that religious people consume less alcohol and have fewer alcohol-related problems.